The potential of biodegradable compostable eco-straw from Lepironia Articulata sp. (Purun/Kercut) - Nurul Farah Anisa, Hairolnizam; Muhammad Amirul Syafiq, Nasarudin; Ali Zainal-Abidin, Mohamad Termizi; Farah, Amalina; Abdul Syukor, Abd Razak; Suryati, Sulaiman (Elsevier Ltd, 2024)
Plastic drinking straws are widely used to drink water and have been shown to be a useful tool in restaurants. Excessive usage, on the other hand, generates a large amount of plastic garbage that is hazardous to the environment and can harm endangered species. According to the findings, subjective norms and perceived behavioral control all have a significant influence on their receptive purpose toward biodegradable drinking straws. The goals of this study were to look into the degradable duration of biodegradable straw, analyse the population of Escherichia coli (E-coli) in biodegradable straw as an indicator of potentially harmful bacteria. An organoleptic evaluation of the straw has been carried out to ensure that the products satisfy the standards set by the organization as well as suit the expectations of the customers. E.coli test for straw hygienity utilising water and waste-water treatment guidelines. In terms of straw structure that can be dissolved in less than 6 months, straws were tested with and without Calcium Hydroxide (Ca(OH)₂) to measure hygiene test. Straw without Ca(OH)2 reached 23 MPN/g and achieved non detected E.coli in this straw treated with Ca(OH)₂. Finally, Lepironia Articulata Sp. (Purun/Kercut) has the potential to become a biodegradable compostable eco-straw and as an alternative to non-degradable plastic straws due to its biodegradable, biocompostable and comparable mechanical properties compared to conventional plastic straws in the current market. The respondents chose biodegradable straws because they can lessen the hazard of ocean waste, reduce microplastics at sea and on land, and are non-toxic. Biodegradable straw from Lepironia Articulata sp. in accordance with the towards sustainable development goals.